Implementation and validation of kV fluoroscopy and CBCT based IGRT protocol for lung SBRT treatment (Revista de Física Médica, 2019)
The aim of this work is to describe our Image-Guided Radiation Therapy (IGRT) protocol for lung Stereotactic Body Radiation Therapy (SBRT) together with the evaluation of the results from applying this protocol over a sample of 47 patients analyzed retrospectively.Simulation time-resolved four-dimensional CT (4DCT) images are acquired taking into account the respiratory cycle of the patient. During the treatment, using VMAT technique, pre- and post- treatment Cone Beam Computer Tomography (CBCT), as well as intrafraction fluoroscopy whenever possible due to lesion position visualization, are performed to verify tumor amplitude motion and position.Fluoroscopy image was acquired in 72% of patients analyzed, from which 71% verified the right position against 29% who needed to be reposition by using intrafraction CBCT at least in one fraction. Post-treatment CBCT systematic and random errors are below 1 mm, thereby protocol validation is accepted.Fluoroscopy manages to verify tumor position accuracy depending on high contrast visualization. However, in comparison to intrafraction CBCT, it involves reducing treatment
Keywords: Image-Guided Radiation Therapy; respiratory motion; intrafraction movement; Stereotactic Body Radiation Therapy